The combination of a neprilysin inhibitor (sacubitril) and angiotensin-II receptor blocker (valsartan) attenuates glomerular and tubular injury in the Zucker Obese rat - Javad Habibi; Annayya R. Aroor; Nitin A. Das; Camila M. Manrique-Acevedo; Megan S. Johnson; Melvin R. Hayden; Ravi Nistala; Charles Wiedmeyer; Bysani Chandrasekar; Vincent G. DeMarco (Cardiovascular Diabetology, 2019)
Abstract Objective Diabetic nephropathy (DN) is characterized by glomerular and tubulointerstitial injury, proteinuria and remodeling. Here we examined whether the combination of an inhibitor of neprilysin (sacubitril), a natriuretic peptide-degrading enzyme, and an angiotensin II type 1 receptor blocker (valsartan), suppresses renal injury in a pre-clinical model of early DN more effectively than valsartan monotherapy. Methods Sixty-four male Zucker Obese rats (ZO) at 16 weeks of age were distributed into 4 different groups: Group 1: saline control (ZOC); Group 2: sacubitril/valsartan (sac/val) (68 mg kg−1 day−1; ZOSV); and Group 3: valsartan (val) (31 mg kg−1 day−1; ZOV). Group 4 received hydralazine, an anti-hypertensive drug (30 mg kg−1 day−1, ZOH). Six Zucker Lean (ZL) rats received saline (Group 5) and served as lean controls (ZLC). Drugs were administered daily for 10 weeks by oral gavage. Results Mean arterial pressure (MAP) increased in ZOC (+ 28%), but not in ZOSV (− 4.2%), ZOV (− 3.9%) or ZOH (− 3.7%), during the 10 week-study period. ZOC were mildly hyperglycemic, hyperinsulinemic and hypercholesterolemic. ZOC exhibited proteinuria, hyperfiltration, elevated renal resistivity index (RRI), glomerular mesangial expansion and podocyte foot process flattening and effacement, reduced nephrin and podocin expression, tubulointerstitial and periarterial fibrosis, increased NOX2, NOX4 and AT1R expression, glomerular and tubular nitroso-oxidative stress, with associated increases in urinary markers of tubular injury. None of the drugs reduced fasting glucose or HbA1c. Hypercholesterolemia was reduced in ZOSV (− 43%) and ZOV (− 34%) (p < 0.05), but not in ZOH (− 13%) (ZOSV > ZOV > ZOH). Proteinuria was ameliorated in ZOSV (− 47%; p < 0.05) and ZOV (− 30%; p > 0.05), but was exacerbated in ZOH (+ 28%; p > 0.05) (ZOSV > ZOV > ZOH). Compared to ZOC, hyperfiltration was improved in ZOSV (p < 0.05 vs ZOC), but not in ZOV or ZOH. None of the drugs improved RRI. Mesangial expansion was reduced by all 3 treatments (ZOV > ZOSV > ZOH). Importantly, sac/val was more effective in improving podocyte and tubular mitochondrial ultrastructure than val or hydralazine (ZOSV > ZOV > ZOH) and this was associated with increases in nephrin and podocin gene expression in ZOSV (p < 0.05), but not ZOV or ZOH. Periarterial and tubulointerstitial fibrosis and nitroso-oxidative stress were reduced in all 3 treatment groups to a similar extent. Of the eight urinary proximal tubule cell injury markers examined, five were elevated in ZOC (p < 0.05). Clusterin and KIM-1 were reduced in ZOSV (p < 0.05), clusterin alone was reduced in ZOV and no markers were reduced in ZOH (ZOSV > ZOV > ZOH). Conclusions Compared to val monotherapy, sac/val was more effective in reducing proteinuria, renal ultrastructure and tubular injury in a clinically relevant animal model of early DN. More importantly, these renoprotective effects were independent of improvements in blood pressure, glycemia and nitroso-oxidative stress. These novel findings warrant future clinical investigations designed to test whether sac/val may offer renoprotection in the setting of DN.